The Determination of Money: A Comparative Analysis of Zakat (Alms) and Income Tax Payers among Selected ASEAN Countries - Shabbir, Malik Shahzad (UIN Sunan Gunung Djati Bandung, 2018)
AbstractThe objective of this study is to provide a solution for ASEAN countries regarding zakat and income tax under Islamic monetary system. When the alms payer spend their alms, they don’t need to pay income tax because they have to deduct already their amount through one channel only. This study based on qualitative measurement technique and includes several constitution acts regarding zakat (alms) payer and income tax acts. This study builds a notion to make the alms as the subtrahend of income tax so it could minimize the burden for those who are obliged to pay both of the tax and alms, where it will lead to a positive impact in terms of increase the number of alms payer and tax payer. The result of these alms are distributed among eight categories set in Quran in order to decrease poverty and boost economic growth in particular countries. The alms payer are disputatively increase then the society will feel welfare of the distributed result of alms to the people. Moreover, everyone has more money to pay taxes especially those belong from low incomes, whose earnings have to be cut again by the income tax paid, which doesn’t mention the religious absolute obligation to pay zakat mal. The study investigates a comparative analysis between two different deduction systems on income. Furthermore, this study also helps policy makers for real implication of alms in the country and creates reform of monetary system for financial institutions.